2019
DOI: 10.1111/srt.12632
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study to evaluate two clinical methods for assessing moisturizing effect on skin barrier repair

Abstract: BackgroundTwo clinical methods of assessing a moisturizer's effect on stratum corneum (SC) barrier repair were evaluated in female subjects with dry skin, to identify an assessment method for future studies.MethodsIn this single‐centre, split‐body study, women with dry skin applied moisturizer before (method A) or after (method B) SC barrier perturbation using D‐Squame® stripping discs. Transepidermal water loss (TEWL) and residual protein on D‐Squame discs were assessed over 14 days.ResultsTwenty‐four subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The skin quality assessment was conducted by the same experienced investigator using the MP6 skin quality evaluation instrument (Courage + Khazaka GmbH, Cologne, Germany). This instrument evaluates several skin qualities with noninvasive probes [ 27 , 28 , 29 ]. Transepidermal water loss (TEWL) as an objective indication of skin barrier function and was estimated using the Tewameter ® TM 300.…”
Section: Methodsmentioning
confidence: 99%
“…The skin quality assessment was conducted by the same experienced investigator using the MP6 skin quality evaluation instrument (Courage + Khazaka GmbH, Cologne, Germany). This instrument evaluates several skin qualities with noninvasive probes [ 27 , 28 , 29 ]. Transepidermal water loss (TEWL) as an objective indication of skin barrier function and was estimated using the Tewameter ® TM 300.…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary tape stripping experiment was conducted on a 30 year old healthy male volunteer’s volar forearm (the 2 cm × 2 cm region was marked) with informed consent, in conjunction with CRS measurement to investigate mechanical and compositional SC variation under physical disruption. To verify the result, transepidermal water loss (TEWL) was used to correlate with the obtained Raman data in this study as it was found to be closely related to skin barrier function and inversely proportional to SC thickness. , A commercial TEWL device (VapoMeter, Delfin) was used to record the evaporation rate value in g/m 2 h followed by CRS measurement. The integration time for each wavelength was 5 s at each depth.…”
Section: Methodsmentioning
confidence: 93%
“…To verify the result, transepidermal water loss (TEWL) was used to correlate with the obtained Raman data in this study as it was found to be closely related to skin barrier function and inversely proportional to SC thickness. 18,19 A commercial TEWL device (VapoMeter, Delfin) was used to record the evaporation rate value in g/m 2 h followed by CRS measurement. The integration time for each wavelength was 5 s at each depth.…”
Section: ■ Methodsmentioning
confidence: 99%